2017
DOI: 10.1051/0004-6361/201629050
|View full text |Cite
|
Sign up to set email alerts
|

Inflowing gas onto a compact obscured nucleus in Arp 299A

Abstract: Aims. We probe the physical conditions in the core of Arp 299A and try to put constraints to the nature of its nuclear power source. − doublet at 119 µm is found redshifted by ∼175 km s −1 compared with other OH and H 2 O lines, suggesting a low excitation inflow. We find that at least two components are required in order to account for the excited molecular line spectrum. The inner component has a radius of 20 − 25 pc, a very high infrared surface brightness ( 3 × 10 13 L ⊙ kpc −2 ), warm dust (T d > 90 K), a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(98 citation statements)
references
References 90 publications
9
89
0
Order By: Relevance
“…In addition to the previously studied case of NGC 4418 (González-Alfonso et al 2012), where the inflow has also been inferred from highangular resolution observations Costagliola et al 2013), the case of Zw 049 where an inverse P-Cygni profile is also observed in the [O i]63 µm line (Falstad et al 2015), the inverse P-Cygni profile of OH119 in Circinus (Stone et al 2016), and the inflow observed in OH119 around Arp 299a (Falstad et al 2017), the clearest examples are the LIRG IRAS 11506−3851 and the ULIRG IRAS 15250+3609. Their OH spec- tra are shown in Fig.…”
Section: Inflowsmentioning
confidence: 78%
“…In addition to the previously studied case of NGC 4418 (González-Alfonso et al 2012), where the inflow has also been inferred from highangular resolution observations Costagliola et al 2013), the case of Zw 049 where an inverse P-Cygni profile is also observed in the [O i]63 µm line (Falstad et al 2015), the inverse P-Cygni profile of OH119 in Circinus (Stone et al 2016), and the inflow observed in OH119 around Arp 299a (Falstad et al 2017), the clearest examples are the LIRG IRAS 11506−3851 and the ULIRG IRAS 15250+3609. Their OH spec- tra are shown in Fig.…”
Section: Inflowsmentioning
confidence: 78%
“…This is in agreement with the fact that most galaxies falling below the fitted correlation show large 9.7 μm silicate strengths as well, S 9.7 m m  −1.5 (see color coding in Figure 6), indicating a similar increase of the dust opacity toward the hot, MIR-emitting background source. Optically thick O I 63 [ ] has been already reported by studies with available information of the [O I] 145 emission line Farrah et al 2013;Rosenberg et al 2015 [ ] ratios lower than half the value of the fit shown in Figure 6 (this threshold is denoted by the dotdashed line), and five of them show clear absorption in the O I 63 [ ] line profile (IRASF08572+3915, NGC 4418, Arp 220, IRASF17207-0014, and IRAS17578-0400), in some cases showing P Cygni or inverse P Cygni profiles indicating outflowing or inflowing gas (González-Alfonso et al 2012;Falstad et al 2015Falstad et al , 2017. Figure 7 shows the Herschel/PACS spectra of these galaxies, where signs of O I 63 [ ] absorption are visually noticeable.…”
Section: Kaufman Et Al 1999) While O I 63mentioning
confidence: 99%
“…4) are evidently nuclear as they have been measured with ALMA. We also expect the 30 µm continuum as measured by Spitzer to be nuclear as well and intrinsically related to H 2 O because H 2 O probes the SED transition from mid-to far-IR wavelengths (González-Alfonso et al 2012;Falstad et al 2015Falstad et al , 2017Aladro et al 2018). No more continuum flux densities (e.g., in the far-IR) are included in the fit because they may be contaminated by extended emission unrelated to H 2 O.…”
Section: Defining the Data Setmentioning
confidence: 99%
“…We have then put a single constraint on the H 2 O abundance as derived above from N H2O and τ 100 , which implicitly assumes a gas-to-dust ratio of 100 by mass. Models that have accounted for the H 2 O absorption and emission in buried galactic nuclei have shown that high H 2 O abundances are inferred in the very warm nuclear cores with T dust 90 K (González-Alfonso et al 2012;Falstad et al 2015Falstad et al , 2017Aladro et al 2018). However, in the more extended regions surrounding these cores where T dust is moderate, X H2O decreases to values < 10 −5 .…”
Section: Likelihood Distributionsmentioning
confidence: 99%